Learning From Artemisia’s Lucretia: Embodied Suffering and Interoception in Suicide - Courtet, Philippe; Guillaume, Sébastien (Frontiers in Psychiatry, 2020)
Artemisia Gentileschi, one of the major painter of the 17th century, produced "Lucretia's Suicide". We would like to emphases, how this painting question our understanding how the psychic pain of suicidal individuals turns into an aggression against the body which is a rather unique process, through the key role of interception and self-awareness. This painting captures in a simple but deeply moving combination of facial expression, body posture, arm movements the suffering caused by psychological pain, a suffering transformed into an aggression against her own body, through self-awareness, Lucretia resolving her inner conflict by ending her life. Then, she harms her body because it is harmful. We will discuss how bodily representations are crucial to interact efficiently and safely with the outside world and to establish one's sense of self as a distinct entity from the rest of the world and the available evidences showing than alterations in the representations of one's own body and the sensations perceived by it contribute to suicide. Indeed, neuroimaging studies show that environmental factors (social stress, social defeat...) together with their biological consequences in the body (increased inflammation, neuroinflammation...) can alter the neural networks of suicidal process by increasing sensitivity to psychological pain, negative emotions and increasing dissociation of self-awareness. Thus, body image, body sensations, body awareness and psychological pain should be examined, through interoceptive measures to understand the dynamic interactions between body, brain and mind underlying suicidal behaviour.